Penegakan Hukum Terhadap Tindak Pidana Judi Togel Sidney di Kota Medan - Yudhanto, Dimas; Munthe, Riswan; Ramadhan, M. Citra (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
This research aims to analyze law enforcement and the judge's considerations in handing down criminal decisions against perpetrators of Sidney gambling crimes in the Medan District Court decision Number 1293/Pid.B/2024/PN Mdn. Law enforcement of criminal acts of gambling shoul be carried out by considering every law and regulation. The research method used is normative juridical with data collection through library research in the form of books and legal journals and criminal regulations. Based on the research results, it was found that the enforcement of punishment in handing down criminal decision was that the Panel of Judges in handing down sentences did not comply with the applicable regulations because they only paid attention to Article 303 of the Criminal Code. The Panel of Judges should also consider Article 27 paragraph (2) of Law Number 19 of 2016, amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE) which contains gambling. This was proven in the process of arresting the defendant, Rabndranath Pilay, who was using internet media by accessing the link www.dewatogel.com in his gambling activities. The judge's consideration in handing down criminal decision was to take into account more non-juridical aspects where the judge looked more at the defendant's background, economic situation and life of the defendant without considering the negative impact of gambling. The panel of judges should give the maximum possible punishment in order to eradicate gambling in society